High-frequency deletion in recovered retrovirus vectors containing exogenous DNA with promoters. - Emerman, M (1984)
We previously described infectious retrovirus vectors constructed from spleen necrosis virus which contain the herpes simplex virus thymidine kinase gene and the mouse alpha-globin gene (K. Shimotohno and H. M. Temin, Nature [London] 299:255-268, 1982). In the present study we report that when TK- chicken cells infected with a virus containing the mouse alpha-globin promoter and other 5' noncoding sequences in addition to the alpha-globin coding sequences were selected for thymidine kinase (TK) activity, all virus-producing TK+ cell clones shed virus with a deletion. These deletions were of different sizes and included the mouse alpha-globin coding sequences and the mouse alpha-globin transcriptional promoter. One of the deleted viruses was molecularly cloned. DNA sequencing showed that the deleted sequences are flanked by a short direct repeat. This deleted virus was also shown to have an advantage over the nondeleted parent both in multiplication and in its specific TK-transforming unit titer. In contrast to the results described above, TK+ cell clones established with viruses that contained only the coding sequences from the mouse alpha-globin gene did not delete and were stable over many cell passages. The implications of the high-frequency deletion of the viruses with internal promoters are discussed in terms of the evolution of retroviruses and the construction of retrovirus vectors.